A permeable reactive barrier for remediating heavy metal contaminated water and method
Patent Information
- Application Number
- CN202211666317.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-23
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2042-12-23
AI Technical Summary
[0003]水体中过量的铜的存在会对人体肝肾等脏器造成损伤,六价铬毒性是三价铬的一百倍,毒性具有更强的致癌和致突变能力,超标的磷会导致水体的富营养化,使水生动植物正常生存环境遭到破坏,铅的过量会对人体组织造成伤害
[0012](1)本发明中以天然矿石或由天然矿石改性或煅烧得到的改性蛭石或赤铁矿为反应介质,对重金属具有良好的吸附效果的同时,反应介质来源广泛,对环境和水质没有污染,更不会产生二次污染,适用于规模化的渗透反应格栅。
Smart Images

Figure BDA0004015211170000081 
Figure BDA0004015211170000082 
Figure BDA0004015211170000091
Abstract
Description
Technical Field
[0001] This invention belongs to the field of water treatment technology, specifically relating to a permeable reactive grid and method for remediating water contaminated with heavy metals. Background Technology
[0002] With industrialization, human exploitation and utilization of mineral resources have intensified. Simultaneously, large quantities of mine tailings have accumulated, leading to increasingly severe soil and groundwater pollution caused by tailings leachate containing heavy metals. my country generates hundreds of millions of tons of tailings annually, and the tailings leachate contains significant amounts of pollutants, such as phosphorus (Pb). 2+ Zn 2+ Cu 2+ Heavy metal cations, SO4 2- Cr2O7 2- Anions, xanthates, No. 2 oils, and other organic pollutants can harm the ecological environment, especially the human living environment.
[0003] Excessive copper in water can damage human organs such as the liver and kidneys. Hexavalent chromium is 100 times more toxic than trivalent chromium and has a stronger carcinogenic and mutagenic effect. Excessive phosphorus can lead to eutrophication of water bodies, destroying the normal living environment of aquatic plants and animals. Excessive lead can damage human tissues.
[0004] Reactive infiltration grid (PRB) technology is an in-situ, passive, efficient, and long-term sustainable remediation technology used to mitigate, intercept, and recover most contaminants present in groundwater. The filling material in the PRB serves as the reaction medium and is the core of the PRB technology. The effectiveness of the reaction medium depends on its reaction with the contaminants; different reaction media can be selected based on the specific contaminants, with the aim of converting the contaminants into non-toxic and stable substances or immobilizing them on the reaction medium.
[0005] Depending on the type of pollutant and the hydrogeological conditions, the medium must be able to adsorb and degrade the pollutant, have long-lasting reactivity, and also have suitable permeability and stability, without causing secondary pollution to the environment. Summary of the Invention
[0006] To address the aforementioned problems, this invention provides a permeable reactive bar (PRB) and method for remediating and removing heavy metal pollutants from water bodies. Vermiculite, zeolite, modified vermiculite, and hematite are used as a composite reactive medium in the PRB to treat polluted water, removing heavy metals and other harmful substances, especially Cu. 2+ Pb 2+ Zn 2+ Mn 2+ Cr2O7 2-This invention purifies water bodies. The reaction medium is derived from natural raw materials, which are widely available, pollution-free, and have a simple and easy processing technology. It achieves good water treatment results, and the reaction medium can be used stably in PRB for a long period. The treatment method is simple, the cost is low, and it is suitable for large-scale application, thus completing this invention.
[0007] The purpose of this invention is to provide a permeable reactive grid (PRB) for remediating water contaminated with heavy metals. In the permeable reactive grid, the reaction medium is selected from one or more of natural or modified natural minerals, preferably one or more of vermiculite, zeolite, hematite, and modified vermiculite, and more preferably one or more of vermiculite, hematite, and modified vermiculite.
[0008] Another objective of this invention is to provide the use of the aforementioned infiltration reactive grid for remediating heavy metal-contaminated water, specifically for remediating Pb-containing water. 2+ Cu 2+ Mn 2+ Zn 2+ and Cr2O7 2- Water contaminated with heavy metals.
[0009] Another object of the present invention is to provide a method for remediating water contaminated with heavy metals, the method utilizing a permeation reactive grid for remediating water contaminated with heavy metals.
[0010] The permeable reactive grid for remediating heavy metal contaminated water provided by this invention has the following characteristics:
[0011] Beneficial effects:
[0012] (1) In this invention, natural ore or modified vermiculite or hematite obtained by modifying or calcining natural ore is used as the reaction medium. It has a good adsorption effect on heavy metals. At the same time, the reaction medium is widely available, does not pollute the environment and water quality, and will not produce secondary pollution. It is suitable for large-scale infiltration reaction grids.
[0013] (2) In this invention, vermiculite, zeolite, modified vermiculite, and hematite obtained by calcining goethite are used as reaction media to react Cu. 2+ Zn 2+ Mn 2+ Cr2O7 2- It exhibits excellent removal performance. In particular, the use of vermiculite, modified vermiculite, and hematite composite as the reaction medium synergistically removes heavy metal ions, improves remediation effects, increases treatment capacity, and extends the service life of the reaction medium.
[0014] (3) In this invention, the particle size, porosity and permeability of the reaction medium are controlled to improve the adsorption capacity of the reaction medium, so that the reaction medium forms a reasonable water flow microchannel, ensuring the treatment volume and treatment effect, avoiding problems such as channeling and blockage of the reaction medium, improving the utilization rate of the reaction medium, extending its service life, and thus reducing maintenance costs. Attached Figure Description
[0015] Figure 1 The XRD patterns of vermiculite and modified vermiculite in this invention are shown.
[0016] Figure 2 The XRD pattern of the zeolite in this invention is shown;
[0017] Figure 3 The XRD patterns of goethite and hematite in this invention are shown;
[0018] Figure 4 The XRD patterns of vermiculite before and after adsorption are shown in Example 8 of this invention;
[0019] Figure 5 The XRD patterns of the modified vermiculite before and after adsorption in Example 8 of this invention are shown.
[0020] Figure 6 The XRD patterns of hematite before and after adsorption in Example 8 of this invention are shown.
[0021] Figure 7 The breakthrough curve of the adsorption column in Example 8 of this invention is shown;
[0022] Figure 8 The breakthrough curve of the adsorption column in Example 9 of this invention is shown;
[0023] Figure 9 The breakthrough curve of the adsorption column in Example 10 of this invention is shown;
[0024] Figure 10 The breakthrough curve of the adsorption column in Example 11 of this invention is shown;
[0025] Figure 11 The diagram shows the pH value variation curves of the effluent from the adsorption column in Examples 8-11 of this invention. Detailed Implementation
[0026] The present invention will now be described in detail through specific embodiments, and the features and advantages of the present invention will become clearer and more explicit with these descriptions.
[0027] The present invention provides a permeable reactive grid (PRB) for remediating heavy metal contaminated water. In the permeable reactive grid, the reaction medium is selected from one or more of natural or modified natural minerals, preferably one or more of vermiculite, zeolite, hematite, and modified vermiculite, and more preferably one or more of vermiculite, hematite, and modified vermiculite.
[0028] The modified vermiculite is obtained by adding vermiculite to a surfactant solution, shaking, separating, and drying.
[0029] The surfactant is selected from one or more quaternary ammonium salt surfactants, preferably those containing C. 12 -C 18 One or more of the quaternary ammonium salts of alkyl groups, such as octadecyltrimethylammonium bromide, hexadecyltrimethylammonium bromide (CTAB), tetradecyltrimethylammonium bromide, dodecyltrimethylammonium bromide, dioctadecyldimethylammonium chloride, dihexadecyldimethylammonium chloride, more preferably CTAB.
[0030] The concentration of the surfactant solution is 40-110 mmol / L, preferably 50-100 mmol / L, and more preferably 60-90 mmol / L.
[0031] The molar mass ratio of the surfactant to vermiculite is 1 mol:(200-800) g, preferably 1 mol:(300-700) g, and more preferably 1 mol:(400-600) g.
[0032] The hematite is obtained by calcining natural goethite. The calcination is carried out in air at a temperature of 200-500℃, preferably 250-450℃, more preferably 300-400℃, such as 350℃. The calcination time is 0.5-4 hours, preferably 1-2 hours.
[0033] The specific surface area of the hematite is 60-210 m². 2 / g, preferably 80-180m 2 / g, more preferably 100-150m 2 / g.
[0034] In one embodiment of the present invention, the reaction medium in the infiltration reaction grid for remediating heavy metal contaminated water is a mixture of zeolite and vermiculite, with a mass ratio of 1:(1-2.5), preferably 1:(1-1.5), and more preferably 1:1.
[0035] In another embodiment of the present invention, in the infiltration reaction grid for remediating heavy metal contaminated water, the reaction medium is a zeolite layer and a vermiculite layer, and the heavy metal contaminated water first passes through the zeolite layer or the vermiculite layer, preferably through the zeolite layer first.
[0036] In another embodiment of the present invention, in the infiltration reaction grid for remediating heavy metal contaminated water, the reaction medium is a vermiculite layer, a modified vermiculite layer and a hematite layer, with a mass ratio of 5:(5-45):(10-80), preferably 5:(5-35):(15-70), more preferably 5:(5-25):(20-60), such as 15:15:60.
[0037] In another embodiment of the present invention, in the infiltration reaction grid for remediating heavy metal contaminated water, the reaction medium is a mixed layer of vermiculite, modified vermiculite and hematite, with a mass ratio of 5:(5-45):(10-80), preferably 5:(5-35):(15-70), more preferably 5:(5-25):(20-60), such as 15:15:60.
[0038] Zeolite and vermiculite for the metal ion Pb 2+ Zn 2+ Cu 2+ Mn 2+ All exhibit adsorption and removal properties. Among them, vermiculite has the highest adsorption capacity for various metal cations, particularly Pb. 2+ >Zn 2+ / Cu 2+ >Mn 2+ This is because the adsorption of heavy metal ions by vermiculite is related to the ions themselves; the larger the ionic radius and the smaller the hydration radius, the easier it is for ion exchange to occur. Among them, vermiculite of three particle sizes showed particularly good adsorption of Pb. 2+ The adsorption capacity of Pb showed the greatest change, with a significant increase. This is because under dynamic experimental conditions, the material and pollutant had more sufficient contact time, resulting in a more complete reaction. 2+ Among the three ions, the hydration radius is the smallest, hence the greatest variation. As the zeolite particle size decreases, the time to reach breakthrough and saturation for all four ions increases. This is because the smaller the zeolite particle size, the shorter the time required for heavy metal cations to diffuse into the zeolite lattice, allowing for faster and more efficient adsorption of heavy metals from water. The three particle sizes of zeolite for Pb... 2+ The adsorption capacities were similar, all around 40 mg / g. However, in terms of the adsorption saturation time of the medium, the smaller the particle size, the longer the zeolite could function and the more heavy metal contaminated liquid it could treat.
[0039] This invention has shown through numerous experiments that vermiculite has a positive effect on Cu. 2+ Zn 2+ Mn 2+ It exhibits good adsorption properties; hematite and modified vermiculite show good adsorption properties for anionic Cr2O7. 2- The adsorption effect is good. Using vermiculite, modified vermiculite, and hematite as reaction media, it can effectively remove Cu from polluted water. 2+ Zn 2+ Mn2+ Cr2O7 2- Pollutants.
[0040] The average particle size of the reaction medium is 10-70 mesh, preferably 10-60 mesh, and more preferably 18-50 mesh.
[0041] The porosity of the reaction medium is 20%-70%, preferably 25%-60%, and more preferably 30%-50%.
[0042] The permeability coefficient of the reaction medium is 0.06-1.2 m / d, preferably 0.08-0.8 m / d, and more preferably 0.1-0.4 m / d.
[0043] The specific surface area of the reaction medium is 3-280 m². 2 / g, preferably 4-200m 2 / g, more preferably 5-110m 2 / g.
[0044] Larger particle sizes in the reaction medium result in higher permeability, greater porosity, and better water permeability. Larger particle sizes effectively prevent column clogging caused by adsorbed contaminants. Furthermore, under the same mass conditions, smaller particle sizes result in a larger total surface area; therefore, the adsorption capacity of the reaction medium for heavy metal cations increases as the particle size decreases.
[0045] This invention also provides the use of the aforementioned infiltration reactive grid for remediating heavy metal contaminated water, specifically for remediating Pb-containing water. 2+ Cu 2+ Mn 2+ Zn 2+ and Cr2O7 2- Water contaminated with heavy metals.
[0046] In the infiltration reactive grid for remediating heavy metal contaminated water: the reaction medium reacts with Pb 2+ The adsorption capacity is 6-15 mg / g, preferably 8-11 mg / g; the reaction medium has a positive effect on Cu. 2+ The adsorption capacity is 2-10 mg / g, preferably 4-6 mg / g; the reaction medium has a high adsorption capacity for Mn. 2+ The adsorption capacity is 2-8 mg / g, preferably 3-5 mg / g; the reaction medium has a high adsorption capacity for Zn. 2+ The adsorption capacity is 2-8 mg / g, preferably 4-6 mg / g; the reaction medium has a high adsorption capacity for Cr2O7. 2- The adsorption capacity is 2-13 mg / g, preferably 5-11 mg / g.
[0047] The present invention also provides a method for remediating heavy metal contaminated water, the method utilizing the infiltration reactive grid for remediating heavy metal contaminated water.
[0048] The permeable reactive grid (PRB) for remediating heavy metal-contaminated water provided by this invention uses vermiculite, zeolite, hematite, and modified vermiculite as reaction media, and can effectively remove heavy metal ions Cu from contaminated water. 2+ Zn 2+ Mn 2+ Cr2O7 2- This invention offers excellent removal efficiency, high throughput, and a long service life of the reaction medium, enabling continuous and stable treatment of large batches of wastewater. More importantly, the reaction medium is selected from natural ores or obtained from natural ores through simple processing methods. It not only provides excellent remediation effects on polluted water but also avoids secondary pollution. Its wide availability makes it suitable for large-scale application of infiltration reactive grids for the remediation of heavy metal-contaminated water, demonstrating promising application prospects.
[0049] Example
[0050] The vermiculite ore was sourced from Weili County, Xinjiang; the zeolite ore was sourced from Weichang County, Chengde City, Hebei Province; and the goethite was sourced from Chenzhou City, Hunan Province.
[0051] Vermiculite ore is crushed by a crusher and screened to obtain vermiculite with mesh sizes of 10-14, 18-35, and 35-60. Zeolite ore is crushed by a crusher and screened to obtain zeolite with mesh sizes of 10-14, 18-35, and 35-60.
[0052] Preparation of hematite: Goethite is crushed and sieved to obtain 20-50 mesh goethite, which is then calcined in a muffle furnace at 350℃ for 1 hour to obtain hematite.
[0053] Preparation of modified vermiculite: At room temperature, weigh 1.5g of vermiculite with a particle size of 18-35 mesh and put it into a 50mL centrifuge tube. Add 40mL of 0.075mol / L CTAB aqueous solution, seal the tube, shake it in a shaker for 240min, centrifuge and wash it 3-5 times, collect the bottom precipitate, and dry it in a drying oven at 60℃ to obtain modified vermiculite.
[0054] Example 1
[0055] The silica sand is filled into a glass column in the following order: a layer of quartz sand, a layer of reaction medium, and another layer of quartz sand. A filter screen is placed between the quartz sand and the reaction medium to prevent them from flowing through the water. An outlet is located at the top of the glass column, and an inlet is located at the bottom. Filter screens are also placed at the inlet and outlet to prevent quartz sand from being carried out, thus forming an adsorption column. The inner diameter of the glass column is 7.854 cm, the top and bottom quartz sand filling height is 43 mm, the mesh size of the quartz sand is 20-50 mesh, and the weight is 133-149 g.
[0056] Using 15g of 10-14 mesh, 18-35 mesh, and 35-60 mesh vermiculite as reaction media, respectively, with a filling height of 33mm, the porosity of the reaction media was tested to be 44.9%, 44.5%, and 44.4%, and the permeability coefficients were 0.207, 0.160, and 0.123, respectively.
[0057] The quartz sand and reaction medium were packed into the glass column using the above filling method. The total mass was weighed and recorded as m1. After water was passed through, the mass of the glass column was weighed at different time periods until the mass no longer changed and recorded as m2. The porosity of the adsorption column was calculated using formula (1).
[0058]
[0059] Where P is the porosity, m2(g) is the wet weight of the column after it is filled with water, m1(g) is the dry weight of the column before water flow, and ρ is the density of deionized water (g / cm³). 3 v is the total volume of the reaction medium in the adsorption column (cm³). 3 ).
[0060] Determination of permeability coefficient: The permeability coefficient of the medium is estimated by using Darcy's law through the variable head test method. The calculation formula is shown in equation (2).
[0061]
[0062] K is the permeability coefficient of the reaction medium (m / d); a is the area of the titrated water column, 78.54 mm². 2 L represents the filling length of the reaction medium, which is 33 mm in all cases; A represents the cross-sectional area of the adsorption column through which water passes, which is 415.265 mm². 2 t is the time (s) for water to flow through the medium; h1 and h2 are the water head heights at the two measuring points, which are 60 mm and 40 mm respectively in this experiment.
[0063] A nitrate solution containing 20 mg / L of copper, manganese, lead, and zinc (each with a copper, manganese, lead, and zinc ion concentration of 20 mg / L) was prepared to simulate the mixed polluted liquid to be treated. A peristaltic pump was connected to the inlet to pump the polluted liquid into the adsorption column at a flow rate of 0.61 mL / min. The effluent was collected daily, and the concentrations of copper, manganese, lead, and zinc ions in the water sample were measured using ICP (inductively coupled plasma optical emission spectrometry). The data obtained from the tests are shown in Table 1.
[0064] When the effluent concentration C t The breakthrough point is considered to be reached when the initial influent concentration C0 is 5%, and this time is considered the breakthrough time. When the effluent concentration C... t When the initial influent concentration C0 is 95%, it is considered that the adsorption capacity of the medium is basically exhausted, and the adsorption column has reached the adsorption endpoint, which is the saturation time.
[0065] Total amount of adsorbate in total flow m t (mg):
[0066]
[0067] Q represents the influent flow rate, measured in mL / min; t t This represents the water intake time, expressed in minutes.
[0068] Total adsorbed ions q t :
[0069]
[0070] The mass of heavy metal ions adsorbed per unit mass of medium, q w :
[0071]
[0072] C ad =(C0-C t ); m is the mass of the adsorbent, in grams.
[0073] Table 1
[0074]
[0075] The limit value for Class III water quality specified in GB / T 14848-93 is: Cu 2+ ≤1.0mg / L, Zn 2+ ≤1.0mg / L, Mn 2+ ≤0.1mg / L, Pb 2+ ≤0.05mg / L.
[0076] Example 2
[0077] The contaminated liquid was treated according to the method in Example 1, with the only difference being that 15g of 10-14 mesh, 18-35 mesh, and 35-60 mesh zeolite were used as the reaction medium, with a filling height of 33mm. The porosities of the reaction medium were tested to be 33.5%, 33.2%, and 32.9%, respectively, and the permeability coefficients were 0.334, 0.285, and 0.199, respectively. The effluent test results are shown in Table 2.
[0078] Table 2
[0079]
[0080] Example 3
[0081] The contaminated liquid was treated according to the method in Example 1, with the only difference being that 25g of 18-35 mesh zeolite and 25g of 18-35 mesh vermiculite were mixed evenly and used as the reaction medium, with a filling height of 66mm. A nitrate solution of 50mg / L copper, manganese, lead, and zinc (each with a copper, manganese, lead, and zinc ion concentration of 50mg / L) was prepared to simulate the mixed contaminated liquid to be treated. The effluent test results are shown in Table 3.
[0082] Table 3
[0083]
[0084] The limit value for Class III water quality specified in GB / T 14848-93 is: Cu 2+ ≤1.0mg / L, Zn 2+ ≤1.0mg / L, Mn 2+ ≤0.1mg / L, Pb 2+ ≤0.05mg / L.
[0085] According to the test results, Cu 2+ The water quality reached the Class III water quality standard limit specified in GB / T 14848-93 within 36 hours, with a treated water volume of 1317 mL; Mn 2+ It reached the standard limit within 26 hours, treating 952 mL of water; Zn 2+ It reached the standard limit within 30 hours, treating 1098 mL of water; Pb 2+ It reached the standard limit within 70 hours, with a water treatment volume of 2562 mL.
[0086] Example 4
[0087] The contaminated liquid was treated according to the method in Example 3, with the only difference being that the upper layer of the reaction medium consisted of 25g of 18-35 mesh zeolite, and the lower layer consisted of 25g of 18-35 mesh vermiculite, with a filling height of 33mm in both cases. The effluent test results are shown in Table 4.
[0088] Table 4
[0089]
[0090]
[0091] The limit value for Class III water quality specified in GB / T 14848-93 is: Cu 2+ ≤1.0mg / L, Zn 2+ ≤1.0mg / L, Mn 2+ ≤0.1mg / L, Pb 2+ ≤0.05mg / L. According to the test results, Cu... 2+The water quality reached the Class III water quality standard limit specified in GB / T 14848-93 within 14 hours, with a treatment volume of 512 mL; Mn 2+ It reached the standard limit in 6 hours, treating 220 mL of water; Zn 2+ The standard limit was reached within 10 hours, and the treated water volume was 366 mL; Pb 2+ The standard limit was reached within 24 hours, and the water volume treated was 878 mL.
[0092] Example 5
[0093] The contaminated liquid was treated according to the method in Example 1, with the only difference being that 5g vermiculite, 5g modified vermiculite, and 60g hematite were mixed evenly and used as the reaction medium. The particle size of the vermiculite and modified vermiculite was 18-35 mesh, and the particle size of the hematite was 20-50 mesh. A mixed contaminated liquid of copper nitrate, manganese nitrate, zinc nitrate, and potassium dichromate, each with a concentration of 20 mg / L, was prepared. The dichromate concentration was measured using a UV spectrophotometer. The effluent test results are shown in Table 5.
[0094] Table 5
[0095]
[0096] The limit value for Class III water quality specified in GB / T 14848-93 is: Cu 2+ ≤1.0mg / L, Zn 2+ ≤1.0mg / L, Mn 2+ ≤0.1mg / L, Cr2O7 2- ≤0.05mg / L. According to the test results, Cu... 2+ The water quality reached the Class III water quality standard limit specified in GB / T 14848-93 within 180 hours, with a treatment volume of 6588 mL; Mn 2+ It reached the standard limit within 24 hours, treating 878 mL of water; Zn 2+ It reached the standard limit within 46 hours, treating 1683 mL of water; Cr2O7 2- It reached the standard limit within 264 hours, with a treated water volume of 9662 mL.
[0097] Example 6
[0098] The contaminated liquid was treated according to the method in Example 1, with the only difference being that 5g of vermiculite, 20g of modified vermiculite, and 45g of hematite were mixed evenly and used as the reaction medium. The particle size of the vermiculite and modified vermiculite was 18-35 mesh, and the particle size of the hematite was 20-50 mesh. The test results are shown in Table 6.
[0099] Table 6
[0100]
[0101] The limit value for Class III water quality specified in GB / T 14848-93 is: Cu 2+ ≤1.0mg / L, Zn 2+ ≤1.0mg / L, Mn 2+ ≤0.1mg / L, Cr2O7 2- ≤0.05mg / L.
[0102] According to the test results, Cu 2+ The water quality reached the Class III water quality standard limit specified in GB / T 14848-93 within 240 hours, with a treated water volume of 8784 mL; Mn 2+ It reached the standard limit within 144 hours, treating 5270 mL of water; Zn 2+ It reached the standard limit within 168 hours, treating 6148 mL of water; Cr2O7 2- It reached the standard limit within 46 hours, with a treated water volume of 1683 mL.
[0103] Example 7
[0104] The contaminated liquid was treated according to the method in Example 1, except that 10g of vermiculite, 25g of modified vermiculite and 35g of hematite were mixed evenly and used as the reaction medium. The particle size of vermiculite and modified vermiculite was 18-35 mesh, and the particle size of hematite was 20-50 mesh.
[0105] The contaminated solution was replenished regularly every day, and samples were taken at fixed points. The concentration of heavy metal cations was tested using ICP, and the concentration of dichromate was tested using ultraviolet spectrophotometry. The test results are shown in Table 7.
[0106] Table 7
[0107]
[0108] The limit value for Class III water quality specified in GB / T 14848-93 is: Cu 2+ ≤1.0mg / L, Zn 2+ ≤1.0mg / L, Mn 2+ ≤0.1mg / L, Cr2O7 2- ≤0.05mg / L. According to the test results, Cu... 2+ The water quality reached the Class III standard limit specified in GB / T 14848-93 within 264 hours, with 9662 mL treated; Mn 2+ It reached the standard limit in 216 hours, treating 7905 mL of water; Zn 2+ It reached the standard limit after 192 hours, treating 7027 mL of water; Cr2O7 2- The standard limit was reached within 24 hours, and 878 mL of water was treated.
[0109] Example 8
[0110] The contaminated liquid was treated according to the method in Example 7, with the only difference being that 15g of modified vermiculite, 15g of vermiculite, and 60g of hematite were sequentially laid on the lower quartz sand layer, with a filling height of 33mm. The vermiculite and modified vermiculite were 18-35 mesh, and the hematite was 20-50 mesh. The test results are shown in Table 8, and the adsorption breakthrough curve is shown in... Figure 7 As shown in the figure, the pH value of the treated effluent changes as follows: Figure 11 As shown in (a).
[0111] Table 8
[0112]
[0113] The limit value for Class III water quality specified in GB / T 14848-93 is: Cu 2+ ≤1.0mg / L, Zn 2+ ≤1.0mg / L, Mn 2+ ≤0.1mg / L, Cr2O7 2- ≤0.05mg / L.
[0114] The test data shows that Cu 2+ The concentration reached the Class III water quality standard limit specified in GB / T 14848-93 after 370 hours, with a treated water volume of 13608 mL; Mn 2+ The concentration reached the standard limit within 224 hours, with a treated water volume of 8238 mL; Zn 2+ The concentration reached the standard limit after 218 hours, with a treated water volume of 8018 mL; Cr2O7 2- The concentration of the effluent solution was basically 0 mg / L within 250-400 hours, but Cr2O7 2- The curve rises sharply from 0 to 56 hours, and within a short period of time, Cr2O7... 2- The concentration reached the standard limit, then dropped sharply and then rose again. This may be due to the medium's effect on Cr2O7. 2- This is caused by the desorption of ions.
[0115] Example 9
[0116] The contaminated liquid was treated according to the method in Example 8, with the only difference being that hematite, vermiculite, and modified vermiculite were sequentially laid on the lower quartz sand layer. The test results are shown in Table 9, and the adsorption breakthrough curves are as follows: Figure 8 As shown, the pH value of the treated effluent changes as follows: Figure 11 As shown in (b).
[0117] Table 9
[0118]
[0119]
[0120] The limit value for Class III water quality specified in GB / T 14848-93 is: Cu 2+ ≤1.0mg / L, Zn 2+ ≤1.0mg / L, Mn 2+ ≤0.1mg / L, Cr2O7 2- ≤0.05mg / L.
[0121] Cu 2+ The water quality reached the Class III water quality standard limit specified in GB / T 14848-93 within 364 hours, with a treatment volume of 13387 mL; Mn 2+ It reached the standard limit within 262 hours, treating 9636 mL of water; Zn 2+ It reached the standard limit within 284 hours, treating 10445 mL of water; Cr2O7 2- It reached the standard limit within 264 hours, with a treated water volume of 9047 mL.
[0122] Example 10
[0123] The contaminated liquid was treated according to the method in Example 8, with the only difference being that modified vermiculite, hematite, and vermiculite were sequentially laid on the lower quartz sand layer. The test results are shown in Table 10, and the adsorption breakthrough curves are as follows: Figure 9 As shown, the pH value of the treated effluent changes as follows: Figure 11 As shown in (c).
[0124] Table 10
[0125]
[0126] The limit value for Class III water quality specified in GB / T 14848-93 is: Cu 2+ ≤1.0mg / L, Zn 2+ ≤1.0mg / L, Mn 2+ ≤0.1mg / L, Cr2O7 2- ≤0.05mg / L.
[0127] Cu 2+ The water quality reached the Class III water quality standard limit specified in GB / T 14848-93 within 398 hours, with a treated water volume of 14638 mL; Mn 2+ It reached the standard limit within 262 hours, treating 9636 mL of water; Zn 2+ It reached the standard limit within 284 hours, treating 10445 mL of water; Cr2O7 2- It reached the standard limit in 410 hours, with a water treatment volume of 15079 mL.
[0128] Example 11
[0129] The contaminated liquid was treated according to the method in Example 8, except that a uniformly mixed mixture of modified vermiculite, vermiculite, and hematite was laid on the lower quartz sand layer, and the adsorption breakthrough curve was as follows. Figure 10 As shown, the pH value of the treated effluent changes as follows: Figure 11 As shown in (d).
[0130] pH changes were measured using a pH meter, heavy metal cation concentration changes were measured using ICP, and dichromate concentration was measured using an ultraviolet spectrophotometer. The test results are shown in Table 11.
[0131] Table 11
[0132]
[0133] The limit value for Class III water quality specified in GB / T 14848-93 is: Cu 2+ ≤1.0mg / L, Zn 2+ ≤1.0mg / L, Mn 2+ ≤0.1mg / L, Cr2O7 2- ≤0.05mg / L.
[0134] Cu 2+ It reached the standard limit after 356 hours, treating 13093 mL of water; Mn 2+ It reached the standard limit within 260 hours, treating 9562 mL of water; Zn 2+ It reached the standard limit after 270 hours, with a treated water volume of 9930 mL; Cr2O7 2- It reached the standard limit within 360 hours, treating 13,240 mL of water.
[0135] By comparison, when the pollutants reach the Class III standard value of the Groundwater Quality Standard, the combination method of Example 11 among the four filling methods in Examples 8-11 is the best.
[0136] Experimental Example
[0137] Experimental Example 1
[0138] X-ray fluorescence (XRF) tests were performed on vermiculite, zeolite, and hematite, and the cost content of vermiculite, zeolite, and hematite was obtained as shown in Table 12.
[0139] Table 12 (wt%)
[0140] vermiculite 39.93 12.74 18.93 7.15 4.54 3.70 1.84 1.45 - - zeolite 77.340 13.856 0.827 1.158 2.667 3.324 - - 0.032 0.786 Hematite 1.320 0.278 0.212 96.911 0.143 - - 0.054 0.029 0.786
[0141] Experimental Example 2
[0142] Elemental analysis (EA) was performed on vermiculite and modified vermiculite. The results of carbon, nitrogen and hydrogen content analysis are shown in Table 13.
[0143] Table 13 (wt%)
[0144] vermiculite 0.59 0.00 1.091 Modified vermiculite 23.64 1.44 4.470
[0145] It can be seen that the C, N and H content of vermiculite after CTAB modification is significantly increased, suggesting that the CTAB content inserted into the vermiculite interlayer and loaded onto the vermiculite surface is relatively high.
[0146] Experimental Example 3
[0147] X-ray diffraction (XRD) analysis was performed on the unadsorbed vermiculite, modified vermiculite, zeolite, and hematite. The specific XRD patterns are shown below. Figure 1 , Figure 2 and Figure 3 As shown.
[0148] Figure 1 The XRD patterns of vermiculite and modified vermiculite are shown. Comparison with standard cards reveals that the main phases of raw vermiculite are vermiculite, mica, and calcite. The interlayer spacing of the modified vermiculite increases because the modifier CTAB enters the vermiculite interlayer. Figure 2 The image shows the XRD pattern of zeolite. The raw zeolite ore is mainly composed of clinoptilolite and quartz. Figure 3 The image shows the XRD pattern of hematite. According to the standard card, after goethite is calcined at 350℃ for 1 hour, the phase changes from goethite to hematite.
[0149] XRD analysis was performed on the vermiculite, modified vermiculite, zeolite, and hematite that reached the adsorption endpoint in Example 8. Specifically, as follows... Figure 4 , Figure 5 and Figure 6 As shown.
[0150] Comparison of vermiculite before adsorption, modified vermiculite, and hematite:
[0151] d of adsorbed vermiculite and modified vermiculite 001 The values all decreased, which is related to Cu 2+ Mn 2+ Zn 2+ Interlayer replacement of vermiculite interlayer Mg 2+ Ca 2+ The adsorption of organic modifier ions between the modified vermiculite layers is related to the adsorption of these ions. After adsorption, the crystallinity of the vermiculite decreases significantly, and the interlayer spacing of the modified vermiculite decreases significantly. The diffraction peaks of mica in the vermiculite sample do not shift because potassium and other cations in mica cannot undergo ion exchange.
[0152] The adsorbed hematite diffraction peaks did not shift, nor did any new diffraction peaks appear, indicating that Cu... 2+ Mn 2+ Zn 2 + Cr2O72- It did not penetrate into the interior of the hematite crystal, and no new phase was formed by the reaction; its adsorption was mainly surface adsorption.
[0153] Experiment Example 4
[0154] Infrared analysis was performed on vermiculite, modified vermiculite, zeolite, and hematite. In the infrared spectra of vermiculite and modified vermiculite, 3427 cm⁻¹... -1 This is the stretching vibration of water molecules between layers, 1641 cm. -1 This is the bending vibration of -OH groups in the interlayer water, 993 cm. -1 This is the stretching vibration of the Si-O-Si bond in the tetrahedron, 720 cm⁻¹. -1 Corresponding to the in-plane bending vibration of carbonate, 681 cm -1 The absorption peak is the bending vibration peak of RO-Si (R = Al, Fe, Mg, etc. cations), located at 459 cm⁻¹. -1 The peaks represent the bending vibrations of Si-O-Si; compared to vermiculite, the modified vermiculite exhibits peaks in the infrared spectrum between 3100 and 2800 cm⁻¹. -1 The high-frequency absorption peak is due to the CH stretching vibration of the -CH2 and -CH3 groups, at 1476 cm⁻¹. -1 The shear-type variable-angle vibration zone of CH2 indicates that CTAB has been inserted into the vermiculite interlayer or adsorbed onto its surface.
[0155] In the FTIR spectrum of zeolite, at 10¹⁴ cm⁻¹ -1 The strong absorption band at 788 cm⁻¹ is due to the framework vibration of Si-O-Si, while at 788 cm⁻¹... -1 727cm -1 The adsorption peaks at [location] represent the vibrations of Si-O-Si and Al-O-Si in the silicon-oxygen tetrahedra, respectively; the absorption peak of zeolite bound water is located at 1629 cm⁻¹. -1 474cm -1 The absorption at 606 cm⁻¹ is caused by the bending vibrations of Si-O or Al-O; -1 The absorption at this point is caused by the stretching vibration of the tetrahedral structure; 3629cm -1 The absorption at this point is caused by the stretching vibration of OH groups in the zeolite.
[0156] Experimental Example 5
[0157] Physical adsorption tests were performed on vermiculite, modified vermiculite, zeolite, and hematite.
[0158] The specific surface area of goethite increases significantly after high-temperature calcination, reaching approximately 4.9 m². 2 / g, after calcination, the specific surface area of hematite increases to 105.0m². 2 / g.
[0159] The specific surface area of raw vermiculite ore is 6.41 m². 2 With a pore size of 3.84 nm and a specific surface area of 5.567 m² / g, CTAB-modified vermiculite has a specific surface area of 5.567 m² / g. 2 / g, pore size is 4.28nm.
[0160] The specific surface area of zeolite is 21.1 m². 2 / g has a large specific surface area, providing numerous surface sites for adsorption.
[0161] The present invention has been described in detail above with reference to specific embodiments and / or exemplary examples, as well as the accompanying drawings. However, these descriptions should not be construed as limiting the present invention. Those skilled in the art will understand that various equivalent substitutions, modifications, or improvements can be made to the technical solutions and embodiments of the present invention without departing from the spirit and scope of the invention, and all such modifications and improvements fall within the scope of the present invention. The scope of protection of the present invention is defined by the appended claims.
Claims
1. A permeable reactive grid for remediating heavy metal contaminated water, wherein the reaction medium in the permeable reactive grid is a vermiculite layer, a modified vermiculite layer, and a hematite layer, with a mass ratio of 15:15:60; The modified vermiculite is obtained by adding vermiculite to a surfactant solution, shaking, separating, and drying. The hematite is obtained by calcining natural goethite at a temperature of 300-400℃. The surfactant is selected from one or more of octadecyltrimethylammonium bromide, hexadecyltrimethylammonium bromide, tetradecyltrimethylammonium bromide, dodecyltrimethylammonium bromide, dioctadecyldimethylammonium chloride, and dihexadecyldimethylammonium chloride; The concentration of the surfactant solution is 60-90 mmol / L; The mass of vermiculite corresponding to 1 mole of the surfactant is 400-600g; The average particle size of the reaction medium is 18-50 mesh; The porosity of the reaction medium is 30%-50%; The permeability coefficient of the reaction medium is 0.1-0.4 m / d; The specific surface area of the reaction medium is 5-110 m². 2 / g.
2. The use of a permeable reactive grid for remediating heavy metal contaminated water as described in claim 1, characterized in that, Used to repair Pb-containing 2+ Cu 2+ Mn 2+ Zn 2+ and Cr2O7 2- Water contaminated with heavy metals.
3. A method for remediating water contaminated with heavy metals, characterized in that, The method utilizes the infiltration reactive grid for remediating heavy metal contaminated water as described in claim 1.
Citation Information
Patent Citations
Method for electrically removing heavy metals and organic pollutants from soil or sludge
CN103170499A
Layered mineral-quaternary ammonium salt surfactant intercalation composite material and preparation method thereof
CN110451516A
But pollutant permeable reactive wall
CN206089212U